2019
DOI: 10.29271/jcpsp.2019.07.604
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Target-controlled Infusion in Anesthesia Induction during Painless Gastroscopy

Abstract: Board and written informed consent was obtained from all participating subjects. A total of 180 patients with American Society of Anesthesiologists (ASA) I-II, who were scheduled to receive painless fibergastroscopic diagnosis or treatment in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…One important reason was the inhibition of the cardiovascular system by fentanyl analgesics such as propofol and remimazolam, which is related to their pharmacological properties. However, there is a greater decrease in the propofol combined with the alfentanil group, which indicates that RB has a less cardiovascular effect than propofol, and the changes of HR, BP are relatively stable, which is also consistent with the conclusions of previous drug clinical trials [13].…”
Section: Introductionsupporting
confidence: 86%
“…One important reason was the inhibition of the cardiovascular system by fentanyl analgesics such as propofol and remimazolam, which is related to their pharmacological properties. However, there is a greater decrease in the propofol combined with the alfentanil group, which indicates that RB has a less cardiovascular effect than propofol, and the changes of HR, BP are relatively stable, which is also consistent with the conclusions of previous drug clinical trials [13].…”
Section: Introductionsupporting
confidence: 86%
“…(1) e inclusion criteria include the following: those who met the indications for painless gastroenteroscopy; all were 20 to 75 years old and patients had no allergies or contraindications to any of the drugs associated with this study. (2) e exclusion criteria include the following: patients with potentially life-threatening circulatory and respiratory diseases which had not been adequately controlled; hepatic dysfunction (Child-Pugh class C or higher); coagulation disorders; cognitive dysfunction; and pregnant and lactating women. All study subjects were divided into a control group (n � 53 cases) and an observation group (n � 53 cases) using the random-number table method, and there was no statistical difference between the two groups compared with each other in terms of baseline information such as sex, age, BMI, and the American Society of Anesthesiology (ASA) classification (P > 0.05), see Table 1 for details.…”
Section: Patients' General Informationmentioning
confidence: 99%
“…1 As indicated in a large randomized controlled trial, the prevalence of hypoxemia in patients after intravenous (IV) injection of propofol was 20% during painless colonoscopy. 2 Studies have shown that the heavier the bodyweight, the higher the prevalence of hypoxemia. 3 In addition, the high prevalence of hypoxemia may be associated with mortality, myocardial ischemia, brain injury, and the risk of mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%